2018
DOI: 10.1140/epjc/s10052-018-5793-1
|View full text |Cite
|
Sign up to set email alerts
|

Generalised nonminimally gravity-matter coupled theory

Abstract: In this paper, a new generalised gravity-matter coupled theory of gravity is presented. This theory is constructed by assuming an action with an arbitrary function f (T, B, L m ) which depends on the scalar torsion T , the boundary term B = ∇ μ T μ and the matter Lagrangian L m . Since the function depends on B which appears in R = −T +B, it is possible to also reproduce curvature-matter coupled models such as f (R, L m ) gravity. Additionally, the full theory also contains some interesting new teleparallel gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 57 publications
0
31
0
Order By: Relevance
“…Still, there is a long route for understanding the possible astrophysical effects of modified Teleparallel theories of gravity. It might be interesting to follow a similar approach done in this paper for other Teleparallel theories, such as scalar-tensor theories [66][67][68][69][70][70][71][72][73][74][75], non-local theories [76] or theories with non-minimally couplings between matter and gravity [77]. These works will be done in forthcoming studies.…”
Section: Case 4: Ft B =mentioning
confidence: 83%
“…Still, there is a long route for understanding the possible astrophysical effects of modified Teleparallel theories of gravity. It might be interesting to follow a similar approach done in this paper for other Teleparallel theories, such as scalar-tensor theories [66][67][68][69][70][70][71][72][73][74][75], non-local theories [76] or theories with non-minimally couplings between matter and gravity [77]. These works will be done in forthcoming studies.…”
Section: Case 4: Ft B =mentioning
confidence: 83%
“…which is clearly determined through the Weitzenböck connection but can be compared with the Ricci scalar analog that is calculated using the Levi-Civita connection. Coincidentally, it turns out that these scalars are equal up to a total divergence term [47,48], namely…”
Section: A the Teleparallel Equivalent Of General Relativity And Itsmentioning
confidence: 99%
“…In the teleparallel setting, scalar fields have been investigated to a moderate degree, with various extensions having been investigated in the cosmological context [23][24][25][26][27][28]. Furthermore, the effects of the boundary couplings in scalar tensor theories have been discussed in various papers [25,[29][30][31][32][33][34][35][36][37][38][39][40][41]. A recent review on various studies related to dynamical analysis in different cosmological constructions can be found in [42].…”
Section: Introductionmentioning
confidence: 99%